SUBSTANCE ABUSE AND WORK SHIFT AS PREDICTORS OF PSYCHOLOGICAL WELLBEING AMONG PARAMILITARY PERSONNEL IN OWERRI - Ebeh, Richards E. (African Journal of Social and Behavioural Sciences, 2021)
The study investigated substance abuse and work shift as predictors of psychological wellbeing among paramilitary personnel of the Nigeria Security and Civil Defence Corps (NSCDC) in Owerri, Imo State, Nigeria. Two hundred and six NSCDC personnel (119 males and 87 females) within the ages of 23 – 57 years (mean = 45.76, SD = 9.15) were selected through the convenience sampling technique for the study. Two instruments were used for data collection; the Drug Abuse Screening Test by Skinner (1982) and the Psychological Wellbeing Scale (PWB-S) by Ryff (1995). The cross sectional survey design was employed while data was analyzed using hierarchical multiple regression analysis. Findings revealed that high levels of substance use and rotational shift inversely predicted psychological wellbeing among NSCDC personnel in Owerri. The study recommends, among others, that the NSCDC should adopt the use of psycho-education in helping personnel who are vulnerable to substance induced behaviour so as to gain better insight and knowledge of how to withdraw from substance abuse.